2005
DOI: 10.1172/jci200522304
|View full text |Cite
|
Sign up to set email alerts
|

Targeted deletion or pharmacological inhibition of MMP-2 prevents cardiac rupture after myocardial infarction in mice

Abstract: MMPs are implicated in LV remodeling after acute myocardial infarction (MI).To analyze the role of MMP-2, we generated MI by ligating the left coronary artery of MMP-2-KO and WT mice, the latter of which were administered orally an MMP-2-selective inhibitor or vehicle (TISAM). The survival rate was significantly higher in MMP-2-KO and TISAM-treated mice than in control WT mice. The main cause of mortality in control WT mice was cardiac rupture, which was not observed in MMP-2-KO or TISAM-treated mice. Control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
139
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(151 citation statements)
references
References 38 publications
11
139
0
1
Order By: Relevance
“…Our previous study 10 and a recent study by Matsumura et al 22 have demonstrated that the inhibition of MMP 2 activity improves the survival rate after acute MI by preventing cardiac rupture and delays after MI remodeling. A recent study by Wang et al 23 has shown that cardiac-specific, constitutively active MMP 2 expression leads to impaired contraction and diminished responses to inotropic stimulation, indicating that MMP 2 can directly impair cardiac function in the absence of superimposed injury.…”
Section: Role Of Mmp 2 In Po Hypertrophymentioning
confidence: 74%
“…Our previous study 10 and a recent study by Matsumura et al 22 have demonstrated that the inhibition of MMP 2 activity improves the survival rate after acute MI by preventing cardiac rupture and delays after MI remodeling. A recent study by Wang et al 23 has shown that cardiac-specific, constitutively active MMP 2 expression leads to impaired contraction and diminished responses to inotropic stimulation, indicating that MMP 2 can directly impair cardiac function in the absence of superimposed injury.…”
Section: Role Of Mmp 2 In Po Hypertrophymentioning
confidence: 74%
“…The effects of selective MMPi have also been investigated. In a mouse model of MI (18), the administration of MMP-2 selective inhibitor to wild type mice led to a pronounced improvement in their survival rates, as in mice with targeted deletion of the MMP-2 gene, by preventing cardiac rupture, even though no effect on infarct size was observed. Yarbrough et al (51) also demonstrated that the administration of exogenous MMPi to inhibit MMP-2, -3, -9 and -13, but not MMP-1 and -7, may reduce the progression of left ventricular end-diastolic volume after MI.…”
Section: Mmp Inhibitors and Ami In Animal Modelsmentioning
confidence: 99%
“…The nature of collagen in the ECM is determined by the balance between MMPs and TIMPs. The imbalance between MMPs and TIMPs is the major factor responsible for cardiomyocyte and interstitial changes following AMI in the infarcted and remote areas (18)(19)(20).…”
Section: Myocardial Infarction and Mmpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats were orally fed with TISAM suspended in 0.5% w/v methylcellulose 400 solution (WAKO) at a dosage of 5 mg/kg/day, according to a previous protocol (19). Rats were sacrificed on day 21 under deep anesthesia, and hearts were removed and analyzed histologically.…”
Section: Treatment Of Eac With Mmp Inhibitorsmentioning
confidence: 99%